DSC investigation of phase equilibria in the Bi-Pb-Sb system. (October 2016) - Yéo, D.P.; Hassam, S.; Boa, D.; Mikaelian, G.; Rogez, J.
Highlights: Two sections studied by DSC allow to draw the Bi-Pb-Sb phase diagram. The monovariant lines vanish on the binary eutectic Bi-Pb. A ternary peritectic reaction is highlighted at 172.1 °C. Abstract: Two sections at X Bi / X Pb  = 2/3 and X Pb  = 0.6 atomic fraction of the Bi-Pb-Sb system are analysed by Differential Scanning Calorimetry. The graphical representations of both sections are drawn in agreement with the binary side systems and the phase boundaries determined from DSC thermograms suit well above T  = 373.2 K. A transitory peritectic reaction is observed at T  = (445.2 ± 0.5) K. Isothermal sections at 445.25 K and 273.15 K are proposed.